Antitumor Activity of Dehydroxymethylepoxychinomycin (DHMEQ) and Cisplatin Combination in a Model of Disseminated Ovarian Cancer - Sh. R. Kzyrgalin; R. S. Yamidanov; R. A. Amirov; Sh. Kh. Gantsev (Креативная хирургия и онкология)
Introduction. Ovarian cancer (OC) is recognized to be a pressing problem of modern oncology. Cytoreductive surgery and combined therapy based on platinum and taxanes play an important role in OC treatment. The response rate to first-line therapy accounts for about 80–90%. However, most patients relapse and develop resistance to therapy. Thus, the search for new effective drugs and new combinations for OC treatment is an urgent task of modern oncology.Aim. To evaluate in vivo the antitumor activity of dehydroxymethylepoxyquinomycin (DHMEQ) and cisplatin combination in an ovarian cancer model.Materials and methods. An experimental model of disseminated OC in rats was used to evaluate antitumor activity. A strain of ovarian tumor (OT) was transplanted into 200 female Wistar rats. The drugs were administered intraperitoneally. The “median life expectancy” was taken as a benchmark for the quality evaluation of experimental treatment.Results. It was found that DHMEQ and cisplatin combination increased the survival rate by 387% (p = 0.005, log-rank test) compared to the control group and by 91% compared to the group of animals treated with cisplatin (p = 0.003, log-rank test) in mono mode. More than 50% of the animals in the DHMEQ + cisplatin group remained alive on day 73 of the experiment. No animals remained alive in the cisplatin group, and only one rat remained in the DHMEQ group.Discussion. Thus, the obtained data demonstrate a potentiating antitumor effect of the DHMEQ + cisplatin combination by 387% compared to the control group.Conclusion. The results of the experiments demonstrated a potentiating antitumor effect of DHMEQ in combination with cisplatin. DHMEQ in combination with cisplatin manifests high efficacy in an in vivo model of ovarian cancer.